Kaidah Laisa Lī ‘Irqin Ẓālimin Ḥaqqun dan Implementasinya pada Pemanfaatan Tanah Gasab: Laisa Lī 'Irqin Ẓālimin Ḥaqqun Rules and Its Implementation in Utilization Gasab Land - Awal Rifai; Imran Muhammad Yunus; Fikri Muh. Zulfikar (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
This research aims to determine the implementation of the rules of Laisa lī 'Irqin Ẓālim Ḥaqqun and the use of gasab land. This research uses descriptive qualitative (non-statistical) research methods in the form of library research to obtain the necessary data, namely based on phenomena that occur in society, using normative, philosophical and fiqh approaches. The results of the research show that the implementation of this rule shows that injustice does not result in the perpetrator being given the right to the injustice he has committed. So whoever seizes land and then grows crops or builds buildings in it, he has no right to own it by paying for it or leave it by paying something similar unless the owner of the land is happy with the planting or construction carried out by the usurper. It is hoped that the implications of this research will be able to provide benefits and provide additional knowledge for the community in particular and Muslims in general to be careful in using property that does not belong to them, especially using gasab land or land belonging to other people.